代谢工程改造解脂耶氏酵母生产油脂研究进展Advances in biosynthesis of microbial oils in metabolically engineered Yarrowia lipolytica - 沈玉平1,2，陈诗洁1，周迅1，张祖姣1,2 SHEN Yuping1,2, CHEN Shijie1, ZHOU Xun1, ZHANG Zujiao1,2 (Zhongguo youzhi, 2022)
微生物油脂是可再生能源发展的重要方向，近年来通过合成生物学方法和代谢工程技术改造，解脂耶氏酵母的产油水平提高迅速，展现了良好的应用发展前景。从代谢途径关键酶调控、负反馈调节解除、代谢途径关键酶异源表达、乙酰辅酶A和NADPH替代途径构建、强化氧化应激保护、促进脂肪酸分泌、适应性进化和计算机辅助模拟8个方面，梳理总结了代谢工程改造解脂耶氏酵母生产油脂的最新研究进展。通过对现有研究分析发现，廉价底物中的毒性成分影响细胞生长和油脂合成，以及油脂调控网络机制的不完全明晰，是限制解脂耶氏酵母油脂产量提升的主要障碍。为此，可通过设计引入解毒途径，添加解毒剂，或筛选毒性化合物耐受菌，以及利用多组学技术和计算机辅助优化进一步解析代谢调控机制解决此问题。此外，在“双碳”背景下，可在解脂耶氏酵母中引入高效的人造光合作用或碳固定途径，利用二氧化碳生产油脂。 Microbial oils are an important direction for the development of renewable energy. In recent years, the oils production of engineered Yarrowia lipolytica has been rapidly improved through synthetic biology methods and metabolic engineering technology, showing an attractive application prospect. The latest research advances in oils production by Y. lipolytica modified by metabolic engineering were summarized as the follow eight aspects: regulation of key enzymes of metabolic pathways, relief of negative feedback regulation, heterologous expression of key enzymes of metabolic pathways, construction of acetyl-CoA and NADPH alternative pathways, protection against oxidative stress, enhancement of fatty acid secretion, adaptive evolution and computer-assisted simulation. The existing research showed that the toxic components in cheap substrates affecting cell growth and oil synthesis as well as the incomplete clarity of the mechanism of oils regulatory network was the bottleneck restricting the improvement of oils production in Y. lipolytica. Therefore, designing and introducing detoxification pathways, adding antidotes, or screening strain tolerant to toxic compound, as well as further elucidating metabolic regulatory mechanisms using multi-omics techniques and computer-assisted can address this issues. In addition, in a ″ double-carbon″ background, efficient artificial photosynthesis or carbon fixation pathways can be introduced in Y. lipolytica to produce oils with carbon dioxide.